MODERN DIAGNOSTIC AND TREATMENT OF VITAMIN В12 DEFICIENCY - A. L. Krasnovskiy; S. P. Grigor’iev; R. M. Alyokhina; I. S. Ezhova; I. V. Zolkina; E. O. Loshkareva (Klinicist)
An article reflects modern concepts of the etiology of vitamin B12 deficiency including medication-induced conditions. Particular attention is paid to diagnostic algorithm in case of overt and latent forms of deficit. As the method of choice for the diagnosis of vitamin B12 deficiency it is recommended to determine the level of holotranscobalamin and use additional methods for detecting metabolic deficiency of vitamin B12 – to study the levels of homocysteine and methylmalonic acid. Diagnostic algorithms for patients with clinical suspicion of vitamin B12 deficiency and the presence of subclinical deficiency. We reviewed the possibility of vitamin B12 oral preparations to correct low levels of cobalamin in asymptomatic patients, as well as maintenance therapy in patients with clinical signs of vitamin B12 deficiency.